Pembuatan Bibliografi Beranotasi Buku dengan Subjek Agama Islam Koleksi Dinas Perpustakaan dan Kearsipan Kota Sungai Penuh Provinsi Jambi - Vuspita, Inten; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper purpose to describe of making an annotated bibliography of Islamic books collection in the library and archives official of Sungai Penuh City Jambi Province to make it easier to find the Information neded one day later. The mathad used in writing this paper is descriptive mathad. With data collection tecniqver through disect oservation and interviews. Stages in creating annotated bibliography are: (1) the determination title of the book is done with consideration of the avai lability of religious book collection which is still in a good codition; (2) collection of library materials by recording bibliographic data; (3) selection of library materials is done by separating books with religious subjects and books that are not with religious subjects; (4) grauping or clarificat ion; (5) keyword creation is done describing a subject matter; (6) Indexing based on author index, title index, and keyword index; (7) typing bibliographic texts; (8) the final bibliographic manuscript examination can be done by checking.Keyword:annotated bibliography; religious book of Islam